Republic of El Salvador Country Environmental Analysis : Improving Environmental Management to Address Trade Liberalization and Infrastructure Expansion - World Bank (World Bank, Washington, DC, 2020)
El Salvador, a small country with limited national resources, needs to grow through its main comparative advantage, which is its strong culture of competitive businesses. To do so, however, the government needs to ensure that the best affordable environmental management is in place to secure sustainable economic development. The benefits of further improvements to the environmental institutional and regulatory frameworks will be substantial not only to facilitate and sustain trade and infrastructure expansion, but in terms of preserving the natural resource base on which economic growth depends. Moreover, while DR-CAFTA is expected to bring new possibilities for investment and trade, the agreement will also raise the scrutiny and monitoring by El Salvador's trade partners regarding environmental compliance. Maintaining low compliance rates would add unnecessary friction and raise the regulatory risks for investing in the country.